Mechanical behavior and statistical analysis of polyethylene terephthalate glycol - Rajan, Kumaresan (2024)
Businesses have improved quality and production capacity by switching from handcranked to automated technology over the previous 50 years. 3D printing and additive manufacturing (AM) marked a turning point in prototyping. Recently developed methods can generate physical models faster and with more complex geometries, going from designs and prototypes to small-batch production. Fused Deposition Modeling (FDM) is becoming more prominent among prototyping approaches. Complex thermoplastic polymer geometric sculptures are best made with FDM. FDM is the most promising approach for product manufacture since it can compete with standard polymer processing processes. PET-G (polyethylene terephthalate glycol-modified) is a common thermoplastic 3D printing filament. It has a good balance of tensile strength and elongation and is resistant to water, heat, and chemicals. It is usually thought to be waterproof and has excellent thermal resistance. One of the essential features of PETG for 3D printing is that it is less likely to become brittle due to its increased flexibility. As an oil by-product, PETG is not biodegradable despite being completely recyclable. The primary goal of this research was to examine the mechanical properties and structural characteristics of FDM-printed PETG samples by varying the parameters (Infill pattern, raster angle). The samples were printed into three different phases 1) Normal parameters, 2) 4 parameters, and 3) 5 parameters. The mechanical properties (Tensile, bending, and flexural) of PETG specimens were investigated in accordance with ASTM standards. The Response surface methodology (RSM) is then used to analyze the experiment's data to find the parameters that have the most significant effect on mechanical properties. RSM was used to create mathematical models of mechanical qualities to predict desired mechanical parameters with various infill percentages and patterns. In normal parameters, the concentric pattern with a 23° raster angle has a high strength in the tensile properties. The cubic pattern with a 90° raster angle has the best compressive and flexural properties. In 4 parameters, the combination with the rectilinear and concentric pattern has the highest values over the tensile, compressive, and flexural properties. Likewise, in 5 parameters, the combination with the rectilinear and concentric top/bottom pattern has the highest values over the tensile, compressive, and flexural properties. The average tensile properties of the 4 and 5 parameter values were doubled compared with the normal parameters. There is some slight improvement in the compressive properties over the normal parameters on the 4 and 5 parameters printed PETG samples. The difference between the normal printed samples and the other two parameters in the flexural properties were double the values. The maximum flexural strength of 72.05 MPa was achieved in the 5 parameters, and it greatly impacted the flexural properties of the FDM-printed PETG specimens. Also, the regression equations were created using the RSM to achieve the maximum properties using the PETG. Likewise, the effect of the infill pattern and raster angle on the mechanical properties of the printed specimens was analyzed. The Coefficient of determination (R2 ) value is more than 95% in all the models showing that the regression models are a good fit. The RSM evidently depicts that both the infill pattern and raster angle significantly affect the physical characteristics of the FDM parts. In future work, the Layer thickness, air gap, raster angle, infill percentage, and infill pattern can be adjusted to study how printing parameters affect the mechanical properties of printed specimens and improve PETG-based FDM specimens and products.